Synthesis and characterizations of modified Y- Type Hexaferrite Materials for Potential Applications in Various Fields - Suthar, Mukesh (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Synthesis and characterizations of modified Y- Type Hexaferrite Materials; for Potential Applications in Various Fields